Penguatan Pemasaran Digital Bagi UMKM Desa (OHOI) Wain Kabupaten Maluku Tenggara - Rainier Hendrik Sitaniapessy; Erlinda Tehuayo; Merry Margareth Pelupessy; Feky Reken (Jurnal TUNAS, 2022)
This community service is carried out by mapping problems from a situation analysis regarding the development of MSME businesses in Wain village, Southeast Maluku district. The high use of digital information technology and the availability of natural resources owned by Wain Village requires the management of MSME businesses that have a more digital touch. The main problem is the low market penetration ability for MSMEs because marketing management and digital marketing capabilities are still low. This activity was carried out for 3 days to provide a comprehensive understanding of digital marketing management and simple digital training to provide adequate loading capacity. The results of this activity provide understanding and digital capabilities in business development and require the intervention of the government and NGOs who can provide continuous assistance.